Building the capacity of Africa for biosciences in agriculture - Shah, Tushaar; Terry, Eugene R. (TSAP and ILRI, 2006)
The New Partnership for Africa’s Development (NEPAD) has placed agriculture and science at the forefront of Africa’s economic development, and has provided support for the establishment of Biosciences eastern and central Africa (BecA) as one of its centres of excellence. The vision is for BecA to capture the immense potential of ‘new science’ to accelerate agricultural development on the continent and to enable African scientists and institutions to become significant technological innovators as well as users. The facilities at BecA’s hub offers state-of-the-art research laboratories for the biosciences, including genomics, proteomics, gene technology, immunology, bioinformatics and containment facilities for safe genetic manipulation of plants and micro-organisms (e.g. for vaccine development). The BecA hub also provides opportunities for capacity building and training, enhanced by the training partnerships which have been established with African universities, internationally renowned research groups, the CGIAR and a wide range of other appropriate institutions. Financial support for joint training programmes is being provided through agreements with a range of multilateral and bilateral donors. Opportunities exist for fellowships and scholarships to support thesis research for young African women scientists, and scientists from countries engaged in post-conflict reconstruction, visiting scientists, and doctoral and post-doctoral fellows. Support can be offered also for short-term-use of research facilities, short training courses, seminars, workshops and conferences.